2021
DOI: 10.7759/cureus.14433
|View full text |Cite
|
Sign up to set email alerts
|

Co-infection With Hepatitis B in Tuberculosis Patients on Anti-tuberculosis Treatment and the Final Outcome

Abstract: BackgroundThe occurrence of both tuberculosis (TB) and concomitant hepatitis B virus (HBV) is likely to be associated with poor patient outcomes and poor treatment response. ObjectiveTo assess whether tuberculosis patients with concomitant hepatitis B virus infection were prone to poorer outcomes and treatment response. MethodologyA case-control study was undertaken at the Tuberculosis Centre,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…However, one study found that patients who received antiviral drugs shortly after being diagnosed with TB had a lower risk of liver damage caused by anti-TB drug hepatotoxicity (3). Based on the risks listed above, a series of worldwide studies set out similar tasks as in the present study to establish the prevalence rates of viral hepatitis in TB patients in order to assess their potential risk (1,2,11,(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 95%
“…However, one study found that patients who received antiviral drugs shortly after being diagnosed with TB had a lower risk of liver damage caused by anti-TB drug hepatotoxicity (3). Based on the risks listed above, a series of worldwide studies set out similar tasks as in the present study to establish the prevalence rates of viral hepatitis in TB patients in order to assess their potential risk (1,2,11,(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 95%
“…Un reciente metaanálisis que incluyó más de 15.000 pacientes ha mostrado que la coexistencia de VHC en pacientes con TB alcanza el 7% 18 . Los pacientes coinfectados resultan de particular importancia, dado que algunos reportes de casos han mostrado que la aparición concomitante de estas dos patologías se asocia con una mala respuesta al tratamiento [19][20] . Más aún, un estudio de casos y controles demostró que los pacientes diagnosticados con tuberculosis e infección concomitante por el virus de la hepatitis B mostraron peor respuesta al tratamiento en comparación con pacientes con TB sin HVC (<0.001).…”
Section: Discussionunclassified
“…In-hospital comorbidity data were obtained from the chief complaints of patients, which is consistent with the review results after admission to the hospital. For reflecting the nutritional status of research objects, this study converted the height and weight into the body mass index (BMI) according to Medical Nutrition Treatment of Overweight/Obesity in China (2021), where BMI values less than 18.5 kg/m² are considered underweight, BMI values from 18.5 to 24.99 kg/m² are normal weight. BMI values > 25 kg/m² were overweight or obese (Chen et al, 2004;Sahile et al, 2021).…”
Section: Data Collectionmentioning
confidence: 99%